DAUR ULANG SAMPAH PLASTIK MENJADI PRODUK BERNILAI DALAM MENDUKUNG KELESTARIAN LINGKUNGAN - Delfy Lensari; Yuli Rosianty; Ika Paridawati; Ideliastuti Ideliastuti (Jurnal Agro Dedikasi Masyarakat (JADM), 2024)
Waste is a national and global problem that requires comprehensive handling. The 3R Reduce, Reuse, Recycle program can reduce environmental problems and support a green economy through improving the waste management process. Recycling is sorting waste according to type so that it can be reused into usable items. Examples include plastic, cans, paper, metal and glass waste. The aim of this service activity is to increase the skills of the Women's Farmer Group in recycling plastic waste into reusable goods. This service activity was carried out in collaboration with UM Palembang KKN students. The location of this community service activity is the Women's Farmers Group (KWT) Tanjung Raman Village, South Prabumulih District, Prabumulih City, South Sumatra Province. The methods used in carrying out activities include providing outreach, putting up banners for throwing away rubbish and carrying out training on recycling plastic waste into items that can be reused. The results of this service can help housewives manage plastic waste into reusable goods and support environmental sustainability